A decoupling analysis framework for agricultural sustainability and economic development based on virtual water flow in grain exporting. (August 2022) - Xu, Yaowen; Man, Xinru; Fu, Qiang; Li, Mo; Li, Haiyan; Li, Tianxiao
Highlights: A model-based analysis framework is developed for economic-environmental nexus in grain trade. Virtual water, footprint, LMDI and Tapio decoupling models are coupled. Effects of grain trade on agricultural sustainability and driven factors are assessed and captured. A real case study provides decoupling relationship, plantation tendency and control measures for sustainable agriculture. Abstract: With the growth in the agricultural economy, the problem of agricultural sustainability has become increasingly prominent. This study proposes a decoupling analysis framework for economic development and multidimensional sustainability indicators in grain exporting by integrating the Tapio decoupling model with virtual water (VW) theory, the Logarithmic Mean Divisia Index (LMDI) model and the footprint method. This framework is advantageous for coordinating research on the problems of virtual water flow (VWF) and ecological consumption for different grains, decoupling economic development and multidimensional sustainability indicators, and identifying key drivers that promote decoupling and curb VW consumption. This framework is applied to a real-world case study in Heilongjiang Province, China. The results show that (1) the final water consumption coefficient of agriculture is the major positive influencing factor of VWF in grain exporting; (2) increasing the export volume of rice and corn instead of soybeans is beneficial for improving agricultural sustainability; and (3) promoting the coordination of multidimensional sustainability indicators effectively improves decoupling levels and relies on the contradiction between agricultural economic growth and environmental sustainability relief in the grain trade rather than on a single index..